Immune niches for hair follicle development and homeostasis - Kiselev, Artem; Park, Sangbum (Frontiers in Physiology, 2024)
The hair follicle is a dynamic mini-organ that has specialized cycles and architectures with diverse cell types to form hairs. Previous studies for several decades have investigated morphogenesis and signaling pathways during embryonic development and adult hair cycles in both mouse and human skin. In particular, hair follicle stem cells and mesenchymal niches received major attention as key players, and their roles and interactions were heavily revealed. Although resident and circulating immune cells affect cellular function and interactions in the skin, research on immune cells has mainly received attention on diseases rather than development or homeostasis. Recently, many studies have suggested the functional roles of diverse immune cells as a niche for hair follicles. Here, we will review recent findings about immune niches for hair follicles and provide insight into mechanisms of hair growth and diseases.The development of hair follicles has been well-characterized by several studies (Park, 2022;Wang and Higgins, 2020;Wang et al., 2022;Welle, 2023) (Figure 1A). The first signs of hair placodes can be seen at 4-8 weeks EGA (Estimated gestational age) which is the equivalent of 2-4 PCW (post-conception weeks) in humans and day E9.5-E12.5 in mice. The first signal initiating the process of placode formation